FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DISMENORE PADA MAHASISWA SEMESTER VIII UNIVERSITAS JENDERAL SOEDIRMAN PURWOKERTO - Tia Martha Pundati; Colti Sistiarani; Bambang Hariyadi (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2016)
Dysmenorrhea is pain during menstruation which is often experienced by women. Family history, age of menarche, length of menstruation, smoking habit, physical activities and stress are risk factors of dysmenorrhea. 8th semester students activity can lead to stress that trigger dysmenorrhea. The purpose of this study was to discover factors related to incidences of dysmenorrhea in 8th semester students of UNSOED. The type of this study was descriptive. The research population was 8th semester students of UNSOED totaling in 1.563 people. The sample was 85 people collected by propotional stratified random sampling technique. Data collection was performed by interviewing using questionnaire. Univariat statistical analysis showed that 67,1% respondent had dysmenorrhea, 57,6% respondent had age of menarche >12years, 71,8% respondent had no family history, 55,3% had long period >7 days, 50,6% had stress, and 51,7% had routine physical activities. Bivariat statistical analysis by chi-square test showed that there was a significant relation between menstruation and dysmenorrhea in 8th semester students with p = 0,03 (p < 0,05); there was a significant relation between stress level and incidence of dysmenorrhea in 8th semester students with p = 0,023 (p > 0,05). Factors not related to incidences of dysmenorrhea were age of menarche, family history, and exercise habit. Therefore, 8th semester students should manage stress to prevent dysmenorrhea and Soedirman Health Centre should provide better services for patients with dysmenorrhea.